Juridical Analysis Of Iran's Weapon Conflict With Israel In The Perspective Of International Humanitarian Law - Phattanasin, Korntima; Zazulki, Ridho; Hudaini, Zavina; Anggraini, Weli; Hasan, Yunica; Handayani, Yosi (Jurnal Hukum Malahayati, 2025)
This research is motivated by the weapons conflict that occurred in Iran and Israel which is based on humanist conflict and its resolution using International Humanitarian Law. The urgency of this research is to find out the obstacles in resolving the conflict between Israel and Iran. The method used is normative legal research or library research, namely legal research by examining library materials or secondary data consisting of primary legal materials. The result of this study is that the two countries have basically configured their armed forces not to fight each other but to serve broader strategic goals: Israel must defend its territory and borders from hostile neighbors, including through forward operations, while Iran must protect its government and project itself into asymmetric conflicts. But their power structures have been defined by wars of survival rather than conquest. The conclusion to this study is that the resolution of this conflict requires greater international attention and cooperation in law enforcement to prevent further violations and promote a just peace. Without a deep resolution to these fundamental issues, a long and stable peace between Iran and Israel seems difficult to achieve. This research recommends that efforts to support the implementation or application of International Humanitarian Law need to be increased to prevent as many violations of this Humanitarian Law as possible, address the abuse of militant groups and third parties, strengthen civilians, and increase cooperation in countering nuclear weapons. Keywords: Arms Conflict, International Humanitarian, Humanity.